Bleach. 29, The slashing opera - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2009)
Ichigo "Strawberry" Kurosaki never asked for the ability to see ghost, he was born with the gift. When his family is attacked by a Hollow, a malevolent lost soul, Ichigo becomes a Soul Reaper, dedicating his life to protecting the innocent and helping the tortured spirits themselves find peace.